Iqbal’s Ideology of Nationalism: A Quranic Perspective: اقبال کا نظریہ قومیت قرآن مجید کے تناظر میں - Bukhari, Dr. Saeed Ahmed (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
With regard to commonalities and unity, the communion of race, communion of home land and communion of languages are common. Islam abhors the differences of color, race, language and country, and bases its Ummah on the religious creed. The concept of oneness of Allah of the Muslims is cementing force for all Muslims and makes them dominant over all the nations of the world. No force of the World can sustain before it. The word "Nation" has been taken in broader sense of words. But in concept of nation, the word "Nation" has been called as Ummah of prophets. Islam has given the Muslims superiority to other nations. And it is distinction of Islam. Universality of Islam has been proved by Iqbal calling the entire Muslims universal and single nation.